PRINSIP PRINSIP DALAM HUKUM KEPAILITAN DALAM PENYELESAIAN UTANG DEBITUR KEPADA KREDITUR - Herry Anto Simanjuntak (JURNAL JUSTIQA, 2020)
In the world of trading, debt and credit is a common and natural thing if a business actor wants to develop his business more advanced, namely by seeking loans from other company partners to get business capital with an agreement to be paid later, and if able to pay according to the specified time then the company is in a "Solbavel" state and vice versa if the company is unable to pay its debt in such a situation it is called "Insolbavel" meaning that it is unable to pay its debts and the condition continues to decline and to the nadir it stops paying until it is finally declared bankrupt by the Court. Bankruptcy is one of the commercial solutions to get out of the debt problem that crushes a debtor, where the debtor is no longer able to pay his debt owed to the creditor so that if the debtor is aware of the inability to pay the maturing obligation, the debtor is aware of the steps. To apply for a voluntary petition for self-bankruptcy is a possible step, or the Court's determination of bankruptcy against the debtor if it is later found that the debtor is no longer able to pay his debts that are due and can be collected as the description above (involuntary petition bankrupty). Bankruptcy is a condition in which the debtor is unable to make payments on the debt owed by the creditor. The inability to pay is usually caused by financial difficulties and the debtor's business is experiencing a decline. Meanwhile, bankruptcy is a court decision which results in general confiscation of all assets of bankrupt debtors, both existing and future ones. The management of bankruptcy settlement is carried out by the curator under the supervision of the supervisory judge with the main objective of using the proceeds from the sale of the assets to pay all debts of the bankrupt debtor proportionally and in accordance with the creditor structure. The bankruptcy process begins with an application for bankruptcy against a debtor who meets the requirements, in accordance with Article 2 paragraph 1 of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (Bankruptcy Law) which states that "A debtor who has two or more creditors and does not pay in full at least one overdue debt which can be declared bankrupt by a court decision, either on its own request or at the request of one or more of its creditors ”. In settling debtors' debts against creditors, there are several principles that can be used by judges in deciding a case, including the Creditorium Parity Principle, the Pari Passu Prorata Parte Principle, the Strured Creditors Principle, the Debt Collection Principle, the Debt Polling Principle and the Universal Territorial Principle.